Himalayan voices : an introduction to modern Nepali literature - Hutt, Michael (Michael J.) (University of California Press, 1991)
While the natural splendor of Nepal has been celebrated in many books, very little of the substantial body of Nepali literature has appeared in English translation. Himalayan Voices provides admirers of Nepal and lovers of literature with their first glimpse of the vibrant literary scene in Nepal today. An introduction to the two most developed genres of modern Nepali literature-poetry and the short story-this work profiles eleven of Nepal's most distinguished poets and offers translations of more than eighty poems written from 1916 to 1986. Twenty of the most interesting and best-known example.
Translated from Nepali.
Keywords: Nepali poetry -- 20th century -- Translations into English.; Short stories, Nepali -- Translations into English.; Authors, Nepali -- 20th century -- Biography.; Nepal -- Literary collections.; Écrivains népalais -- 20e siècle -- Biographies.; TRAVEL -- Special Interest -- Literary.; LITERARY CRITICISM -- General.; LITERARY CRITICISM -- Asian -- General.; Authors, Nepali; Nepali poetry; Short stories, Nepali; Nepal; Literatur; Anthologie; Littérature népalaise -- 20e siècle -- Traductions anglaises.; Littérature népalaise -- Histoire et critique.; Nepali.; 1900-1999; Nepali literature; Biographies; Literary collections; Translations; Biographies.